2017
DOI: 10.20961/jphystheor-appl.v1i2.19312
|View full text |Cite
|
Sign up to set email alerts
|

Time Variation of Insertion Cu On TiO2 Nanoparticles Layer Through The Electroplating Method In Dye-Sensitized Solar Cell (DSSC)

Abstract: Abstract:Copper (Cu) is a conductive metal. Insertion of copper on a TiO 2 active layer is the right choice in the effort to improve Dye-Sensitized Solar Cell (DSSC) performance. Electroplating methods were used in this study to insert copper in the TiO 2 layer. The device of DSSC used in this study is natural dye Moringa Oleifera, TiO 2 -Cu electrode, the counter electrode of Pt and electrolyte from NaI. The peak absorbance of dye is at wavelength 415 nm and maximum efficiency is 0,093% from the time variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…After the sun's rays fall on this material, active oxygen is generated, which in turn purifies water from pollutants, bacteria, fungi, germs, organic materials, as well as toxic elements such as arsenic As and Chromium Cr [1][2][3]. Titanium was first discovered in 1971 by an English chemist and geologist William Gregor And years later, titanium dioxide TiO 2 was manufactured for use as a whitening ingredient used in toothpastes, a multifaceted compound used as a strong photocatalyst capable of breaking any organic compound if exposed to the sun [4][5][6][7][8][9][10][11][12][13][14][15], and therefore can be used in cleaning and bleaching fabrics and purifying water / waste water and air [16] and in many other industrial applications such as the iron, electronics and chemicals industry, all the way to the manufacture of cosmetics, batteries and solar cells [17] and hydrogen production because of its important physical and chemical properties. It has chemical stability and is chemically non-toxic [2,3] and a high static permittivity, and is characterized by an Eg energy gap ranging between 3.04-3.46 eV [18], as it has A high resistivity estimated at 10 12 Ω.cm at a temperature of 25C°.…”
Section: Introductionmentioning
confidence: 99%
“…After the sun's rays fall on this material, active oxygen is generated, which in turn purifies water from pollutants, bacteria, fungi, germs, organic materials, as well as toxic elements such as arsenic As and Chromium Cr [1][2][3]. Titanium was first discovered in 1971 by an English chemist and geologist William Gregor And years later, titanium dioxide TiO 2 was manufactured for use as a whitening ingredient used in toothpastes, a multifaceted compound used as a strong photocatalyst capable of breaking any organic compound if exposed to the sun [4][5][6][7][8][9][10][11][12][13][14][15], and therefore can be used in cleaning and bleaching fabrics and purifying water / waste water and air [16] and in many other industrial applications such as the iron, electronics and chemicals industry, all the way to the manufacture of cosmetics, batteries and solar cells [17] and hydrogen production because of its important physical and chemical properties. It has chemical stability and is chemically non-toxic [2,3] and a high static permittivity, and is characterized by an Eg energy gap ranging between 3.04-3.46 eV [18], as it has A high resistivity estimated at 10 12 Ω.cm at a temperature of 25C°.…”
Section: Introductionmentioning
confidence: 99%
“…Obina et al [30] reported the cell of Cu/TiO 2 nanoparticle was deposited on the FTO glass used the spin coating method. Layers of Cu/TiO 2 nanocomposite were prepared in variations at 1, 2 and 3 layers.…”
Section: Modification Of Tio 2 Electrode With Copper Oxidementioning
confidence: 99%